Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1007/bf02368135
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a phosphene-based visual field: Visual acuity in a pixelized vision system

Abstract: A visual prosthesis for the blind using electrical stimulation of the visual cortex will require the development of an array of electrodes. Passage of current through these electrodes is expected to create a visual image made up of a matrix of discrete phosphenes. The quality of the visual sense thus provided will be a function of many parameters, particularly the number of electrodes and their spacing. We are conducting a series of psychophysical experiments with a portable "phosphene" simulator to obtain est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(112 citation statements)
references
References 26 publications
3
108
0
1
Order By: Relevance
“…Cha and colleagues 70 and Cha, Horch and Normann 71 used psychophysical studies to determine the minimum number of electrodes required to be able to read letters. They showed that 625 electrodes in a 25 by 25 array with a centre-to-centre spacing of 400 mm all contained within a 1.0 cm by 1.0 cm grid 71 allowed resolution of images in a tiny central field.…”
Section: Design Of the Electrode Arraymentioning
confidence: 99%
See 1 more Smart Citation
“…Cha and colleagues 70 and Cha, Horch and Normann 71 used psychophysical studies to determine the minimum number of electrodes required to be able to read letters. They showed that 625 electrodes in a 25 by 25 array with a centre-to-centre spacing of 400 mm all contained within a 1.0 cm by 1.0 cm grid 71 allowed resolution of images in a tiny central field.…”
Section: Design Of the Electrode Arraymentioning
confidence: 99%
“…They showed that 625 electrodes in a 25 by 25 array with a centre-to-centre spacing of 400 mm all contained within a 1.0 cm by 1.0 cm grid 71 allowed resolution of images in a tiny central field. For navigational tasks, a lower resolution but larger field of view was necessary.…”
Section: Design Of the Electrode Arraymentioning
confidence: 99%
“…Os pesquisadores devem ainda definir os parâmetros elétricos para a segurança e efetividade de um pixel. Alguns estudos mostraram que 625 pixels podem ser a estimulação mínima para criação de uma imagem simples (41) . A eficácia da estimulação elétrica nos tecidos pode ser influenciada pela propriedade elétrica da célula alvo, pela distância dos eletrodos até a célula alvo, impedância dos tecidos, relação entre os limiares de corrente elétrica, pela duração da ativação neuronal e pela influência de estímulos repetitivos na via visual (42)(43)(44) .…”
Section: B -O Uso De Energia Elétrica Para Criação De Implantes Eletrunclassified
“…On the other hand, the number of stimulation sites/channels is very high. Indeed, for a meaningful image to be perceived by the user, hundreds of stimulation sites are expected to be required [10]. This puts severe constraints on the external to internal (downlink) data rate and the total power efficiency of the device.…”
Section: Introductionmentioning
confidence: 99%